The Duration Effectivity of Diode Laser 405 nm with Erythrosine Photosensitizer in Killing Streptococcus Mutans - Sri Kunarti; Anin Dita; Widya Saraswati (Conservative Dentistry Journal, 2020)
Introduction: Dental caries is a multifactorial disease caused by the interaction of pathogenic bacteria, especially Streptococcus mutans. Various caries prevention chemically and mechanically can help reduce the number of bacteria. However, this approach does not cover the entire bacterial population with a photodynamic therapy approach with the addition of photosensitizers and low-intensity light radiation with the right wavelength able to eliminate the number of S. mutans bacteria. Purpose:To determinethe duration of effective irradiation time on a 405 nm diode laser with erythrosine photosensitizer in killing S. mutans bacteria.Methods: This research was an experimental laboratory type with 25 S. mutans samples divided into 5 groups treated with erythrosine photosensitizer 0.1 mg / ml and 405 nm diode laser irradiation with 45 seconds, 60 seconds, 75 seconds duration and no erythrosine photosensitizers and without irradiation. The growth of S. mutans bacteria was calculated then the data were analyzed statistically.Results:the research found that S. mutans bacteria decreased gradually in each group; erythrosine without photosensitizer and without irradiation had the highest average growth rate of 71.6 CFU / ml; without photosensitizer with irradiation of 40.6 CFU / ml; irradiation with photosensitizer 45 seconds at 20.6 CFU / ml; irradiation with 60 seconds photosensitizer at 11 CFU / ml; and irradiation with 75 seconds photosensitizer at 0 CFU / ml. In statistical tests, the data are normally distributed and homogeneous. There are significant differences between groups.Conclusion: The effective duration in this study was found at 75 seconds.